Murder one William Bernhardt.. - Bernhardt, William, 1960- (Ballantine Books, 2001)
Tulsa defense attorney Ben Kincaid faces his own day in court after a major technical blunder on the part of overzealous cops frees Kincaid's client, stripper Keri Dalcanton, who had been on trial for the brutal murder of a veteran police detective.